2020
DOI: 10.1063/5.0015246
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman spectroscopy for chemical and biological sensing using nanoplasmonics: The relevance of interparticle spacing and surface morphology

Abstract: In this review, the weightiest decadal developments of surface-enhanced Raman scattering (SERS) and nanoplasmonic materials in sensing applications are discussed. Today, there are several well-established research directions where plasmonic detection is employed extensively, namely, food and water quality monitoring, viruses, pathogenic bacteria and hazardous toxin investigations for theranostic applications, and explosive substance detection for military and civil protection purposes. A combination of vibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 305 publications
1
84
0
Order By: Relevance
“…Additionally, instead of the outstanding flexibility, the L-PTFE-Ag membrane can be used to develop high-performance SERS substrates because of the LSPR effect and 3D micro-/nano-structures. The 3D micro-/nano-structures are helpful to enhance the internal light reflection, leading to the improvement of SERS performance [66][67][68][69][70][71]. In order to characterize microstructures of samples, CLSM was used to examine the surface morphology of PTFE, L-PTFE, and L-PTFE-Ag (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, instead of the outstanding flexibility, the L-PTFE-Ag membrane can be used to develop high-performance SERS substrates because of the LSPR effect and 3D micro-/nano-structures. The 3D micro-/nano-structures are helpful to enhance the internal light reflection, leading to the improvement of SERS performance [66][67][68][69][70][71]. In order to characterize microstructures of samples, CLSM was used to examine the surface morphology of PTFE, L-PTFE, and L-PTFE-Ag (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of these two advantages mentioned above plays a vital role in developing PTFE-based SERS substrates. Appropriate diameter and spacing of silver nanoparticles (AgNPs) will help to improve the SERS performance [1,69,72]. As a pioneer, Kumar et al reported flexible SERS substrates with AgNPs on grating PDMS structures that combine LSP and surface plasmon polariton structures [73,74].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, to achieve SERS, the Raman active molecule is placed within the localized electric field of the plasmonic nanostructures such that the molecule will experience an increased Raman scattering cross-section and hence, enhanced Raman signal (Barbillon, 2020;Hamm, Gee, & De Silva Indrasekara, 2019;P. Li et al, 2020;Shvalya, Filipič, Zavašnik, Abdulhalim, & Cvelbar, 2020). Due to the specific fingerprints of fluorescence at molecular level, SERS has shown several advantages of high selectivity, single molecule detection, and molecular characterization, and in addition high throughput, point-of-care applicability, and easy sample preparation.…”
Section: Optical and Plasmonics Biosensorsmentioning
confidence: 99%
“…Since the SERS effect was first observed with pyridine which was adsorbed on rough Ag electrode [ 12 ], various techniques have been suggested to develop substrates with enhanced SERS properties. The SERS effect is known to be mediated by two principles, electromagnetic mechanism (EM) and chemical mechanism (CM) [ 13 , 14 , 15 ]. The EM is a long-range effect originated from an enhanced electromagnetic field and it depends on the morphology of the substrate.…”
Section: Introductionmentioning
confidence: 99%